Sağlık çalışanlarının empatik eğilim ve becerilerinin değerlendirilmesi - Çiçek, Aysun (My University, 2006)
Araştırma, sağlık çalışanlarının empatik eğilim ve beceri düzeylerini ve bunlara etki eden faktörlerle ilişkisini belirlemek amacıyla, tanımlayıcı, analitik olarak planlandı ve gerçekleştirildi. Çalışmanın evrenini; Eylül 2005 tarihinde Sakarya Sağlık Müdürlüğünden alınan verilere göre 106 uzman, 100 pratisyen hekim, 225 hemşire ve 115 ebe olmak üzere toplam 546, örneklem grubunu; 90 hemşire, 90 ebe, 50 uzman ve 50 pratisyen hekim olmak üzere toplam 280 sağlık çalışanı oluşturdu. Veri toplanmasında araştırmacı tarafından hazırlanan bilgi formu ve Prof. Dr. Üstün Dökmen tarafından geliştirilen Empatik Eğilim ve Empatik Beceri Ölçekleri kullanıldı. Veri analizinde; oran, ortalama (x), standart sapma (SD), Oneway Anova testi Tukey HDS, Mann Whitney U, Ki-Kare testi, Pearson korelasyon ve Reliability analiz teknikleri kullanıldı. Çalışmamızda Empatik Eğilim ve Beceri Ölçeğinin Güvenirliğinin Cronbach’s Alpha katsayısı, empatik eğilim ölçeği için α= 0,822, empatik beceri ölçeği için α= 0,535 bulunmuş olup, geçerlilik güvenilirlik analizinde sonuçlar % 95’lik güven aralığında, anlamlılık p<0,05 düzeyinde değerlendirildi. Uzman hekimlerin empatik eğilimleri; çocuk sayısına, kliniğe, çalışma, evde hayvan besleme durumuna, empatik becerileri; kliniğe göre anlamlı farklılık gösterdiği saptandı. Hemşirelerin empatik eğilimleri; eğitime, kliniğe, çalışma, mesleği isteyerek seçme, enstrüman çalma, resim ve herhangi bir el sanatıyla uğraşma durumuna, empatik becerileri; eğitim durumuna, kliniğe göre anlamlı farklılık gösterdiği saptandı. Ebelerin empatik eğilimleri; mesleği isteyerek seçme, çalıştıkları kuruma, kliniğe, çalışma durumuna, empatik becerileri; çalışma yılına, eğitim durumuna göre anlamlı farklılık göstermektedir. Pratisyen hekimlerde incelenen değişkenlere göre anlamlı farklılık saptanmadı. 2.

The Evaluation of Empathic Tendencies and Skills of Health Staffs The study is designed and realized as descriptive and analytical for determine purpose that degree of empathic tendencies and skills of health staffs and factors which effect them. In September 2005, it formed the research according to data which are taken from Sakarya City Health Management and these included 106 experts, 100 practicians, 225 nurses and 115 midwifes. They were 546 people. The sample group included 280 people and consisted of 90 nurses, 90 midwifes, 50 experts and 50 practicions. Information by created researcher and Empathic Tendency and Empathic Skills Scales by developed Prof. Dr. Üstün Dökmen had been used in collection of data. In analysis of data these techniques had been used: ratio, average (x), standard deviation (SD), Oneway Anova Test Turkey HDS, Mann Whitney U, Ki-Square test, Pearson corelation and Reliability analysis technique. In consequence of study, so that in our study Reliability coefficient of The Empathic Tendency and Empathic Skills Scale had been evaluated with Alpha method. Cronbach’s alpha coefficient empathic tendency scale () and empathic skill scale () had been found respectively 0.822, 0.535. The validity and reliability of empathic tendency and skill scales had been made with Reliability analysis. The results had been evaluated to 95 % reliance interval and p<0,05 level of meaningfulness. For expert doctors, the empathic tendency levels have difference according to following states: children numbers, clinic,; and the empathic skills have difference according to clinic. For nurses, the empathic tendency have difference according to condition of education, clinic, choosing the occupation with willingly, playing to instruments, painting and dealing with any handicraft; and empathic skills have difference according to following states: education levels and clinic. For midwifes, the empathic tendency have difference according to choosing the occupation with willingly, clinic, situation of work; and the empathic skills have difference according to education levels and years of working. For practician doctors, it had not been fixed any meaningful difference.
Keywords: Empati_Sağlık Personeli; Hemşirelik Hizmetleri